Instant Noodle Consumption Behavior of Undana Public Health Faculty Students Living in Boarding House in Oesapa - Lussy, Heldi Mira Bella; Nur, Marselinus Laga; Toy, Sarci M. (Faculty of Public Health, Nusa Cendana University, 2023)
Fast development technology on era now raises exists shift pattern life on society to be all instant and practical including pattern consumption. Instant noodles is wrong one food lots of instant favored. Behavior consumption noodles instant by part big consumer based on with reason no have enough time for consume a complete meal especially for cook and present it. Consumption noodles that instant too often could increase risk and danger for health. Destination study this for knowing description Instant Noodle Consumption Behavior of Students at Public Health Faculty UNDANA living in bording house in Oesapa. Type study this descriptive with approach qualitative. Location study in bording house Oesapa. Time study conducted from month October until November 2022. Amount informants 10 people namely 8 informants key and 2 informants supporters. Technique determination informant use technique snowball sampling. Data analysis using qualitative data analysis that is data reduction, display data on considered things important, and make conclusion . Results study showing frequency consumption noodles instant on informant 2 up to 5 times deep a week. Amount consumption noodles instant every presentation informant use 1 pack, current menu variations presentation informant add sausage and egg. Time consumption, informants consume noodles instant in time eat afternoon and eat night. Should resident students in cost consume noodles instant no in a manner excessive because could cause problem health like obesity, hypertension and disease other. Addition ingredient other food inside serve noodles instant like vegetables green also need for fulfillment needs the nutrients needed by body.